X-ray crystallographic insights into post-synthetic metalation products in a metal–organic framework. (13th January 2017) - Huxley, Michael T.; Coghlan, Campbell J.; Bloch, Witold M.; Burgun, Alexandre; Doonan, Christian J.; Sumby, Christopher J.
Abstract : Post-synthetic modification of metal–organic frameworks (MOFs) facilitates a strategic transformation of potentially inert frameworks into functionalized materials, tailoring them for specific applications. In particular, the post-synthetic incorporation of transition-metal complexes within MOFs, a process known as 'metalation', is a particularly promising avenue towards functionalizing MOFs. Herein, we describe the post-synthetic metalation of a microporous MOF with various transition-metal nitrates. The parent framework, 1, contains free-nitrogen donor chelation sites, which readily coordinate metal complexes in a single-crystal to single-crystal transformation which, remarkably, can be readily monitored by X-ray crystallography. The presence of an open void surrounding the chelation site in 1 prompted us to investigate the effect of the MOF pore environment on included metal complexes, particularly examining whether void space would induce changes in the coordination sphere of chelated complexes reminiscent of those found in the solution state. To test this hypothesis, we systematically metalated 1 with first-row transition-metal nitrates and elucidated the coordination environment of the respective transition-metal complexes using X-ray crystallography. Comparison of the coordination sphere parameters of coordinated transition-metal complexes in 1 against equivalent solid- and solution-state species suggests that the void space in 1 does not markedly influence the coordination sphere of chelated species but we show notably different post-synthetic metalation outcomes when different solvents are used. This article is part of the themed issue 'Coordination polymers and metal–organic frameworks: materials by design'.